Photocatalytic Degradation Of Phenol By Silica Gel-Supported Titania Nanotubes - Wong, Chung Leng (2012)
TiO2 nanotubes and immobilized TiO2 nanotubes were successfully synthesized by a hydrothermal method and binding method. The produced photocatalysts were characterized by the Brunauer-Emmett-Teller (BET) method, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), transmission electron microscope (TEM) and X-ray diffraction (XRD). The photocatalytic activities of the photocatalysts were evaluated through the photocatalytic degradation of aqueous phenol solution in a batch reactor. TiO2 nanotubes produced at 130 °C for 3 h showed the highest degradation rate of phenol compared with the other samples prepared at 130 °C for 1 h, 5 h and 7 h, complete degradation being achieved in 130 min. Special focus was given in order to determine the optimum composition of each component (catalyst, support and binder) in the immobilization of TiO2 nanotubes. The highest efficiency of phenol degradation was achieved when the ratios of TiO2 nanotubes: silica gel: colloidal silica was 1:2:20. For the comparison, TiO2 nanotubes and immobilized TiO2 nanotubes showed higher photocatalytic activity as compared with pure TiO2. The photocatalytic performance of TiO2 nanotubes and immobilized TiO2 nanotubes achieved 100 % and 98.0 % respectively, of phenol degradation, whereas pure TiO2 attained only 77.0 % degradation. The photocatalytic activity of the immobilized TiO2 nanotubes was slightly decreased after four cycles for phenol degradation.